Pembelajaran Pendidikan Agama Islam Berbasis Proyek - Putri Firdaus Fahmi; Fitria Faradina Kafa Aula; Siti Fatimah; Taufiqurrohman Taufiqurrohman (TSAQOFAH, 2026)
Islamic Religious Education (PAI) learning has a strategic role in shaping students’ character, noble morals, and spiritual awareness. However, the implementation of PAI learning still faces various obstacles, particularly the dominance of conventional teacher-centered methods and the lack of contextual learning experiences, so the internalization of Islamic values has not occurred optimally in students’ lives. This article aims to examine the concept, implementation, advantages, and challenges of project-based PAI learning as an alternative learning innovation relevant to the demands of 21st-century education. This study used a library research method by examining various scholarly sources related to Project-Based Learning and Islamic Religious Education. The findings show that project-based PAI learning can increase students’ engagement in the learning process, develop critical thinking, creativity, collaboration, and communication skills, and strengthen the practice of Islamic values in daily life. Nevertheless, its implementation still faces challenges related to teacher readiness, limited time, and support for facilities and infrastructure. The conclusion of this study confirms that project-based PAI learning can serve as an innovative learning strategy that supports the achievement of Islamic education goals in a more contextual, participatory, and meaningful manner. The implications of this study indicate the importance of systematic lesson planning, improving teacher competence, and institutional support so that project-based PAI learning can be implemented effectively in shaping students’ character and 21st-century skills.